2017
DOI: 10.1002/jcph.988
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Strong CYP3A Inhibition and Induction on the Pharmacokinetics of Ixazomib, an Oral Proteasome Inhibitor: Results of Drug‐Drug Interaction Studies in Patients With Advanced Solid Tumors or Lymphoma and a Physiologically Based Pharmacokinetic Analysis

Abstract: At clinically relevant ixazomib concentrations, in vitro studies demonstrated that no specific cytochrome P450 (CYP) enzyme predominantly contributes to ixazomib metabolism. However, at higher than clinical concentrations, ixazomib was metabolized by multiple CYP isoforms, with the estimated relative contribution being highest for CYP3A at 42%. This multiarm phase 1 study (Clinicaltrials.gov identifier: NCT01454076) investigated the effect of the strong CYP3A inhibitors ketoconazole and clarithromycin and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0
6

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 35 publications
4
31
0
6
Order By: Relevance
“…This contrasted with the essentially nil effect of the CYP3A inhibitor itraconazole. Similar findings of discordance between CYP3A inhibition and induction have been reported for several drugs, including ixazomib, 17 tivozanib, 18 and vandetanib 19 ; this contrast has 1 of 2 possible main explanations. First, the induction of CYP3A-mediated metabolism by rifampin might cause a significant increase in clearance of avadomide, although the contribution of CYP3A to avadomide clearance is small at baseline.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This contrasted with the essentially nil effect of the CYP3A inhibitor itraconazole. Similar findings of discordance between CYP3A inhibition and induction have been reported for several drugs, including ixazomib, 17 tivozanib, 18 and vandetanib 19 ; this contrast has 1 of 2 possible main explanations. First, the induction of CYP3A-mediated metabolism by rifampin might cause a significant increase in clearance of avadomide, although the contribution of CYP3A to avadomide clearance is small at baseline.…”
Section: Discussionsupporting
confidence: 81%
“…This seems to apply to ixazomib, whose PK was well reconciled by a physiologically based PK model incorporating a minor contribution of CYP3A to overall clearance, strong induction of CYP3A4, and moderate induction of intestinal P-gp. 17 Safety assessment indicated that avadomide, administered as a single oral dose of 3 mg alone or coadministered with itraconazole, fluvoxamine, or rifampin, was well tolerated by the healthy subjects in this study. No new observed or suspected risks were suggested by the study results.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…This pleiotropic effect may be contributing to the overall osimertinib metabolism and decreasing exposure. A similar effect has been observed for other agents (tivozanib, ixazomib) where there is no effect with CYP3A inhibitor co-administration, but a clinically meaningful effect when co-administered with rifampicin, which is suggestive of induction of upstream nuclear hormone receptor pathways and multiple enzymes [40][41][42].…”
Section: Discussionsupporting
confidence: 69%
“…Основным механизмом клиренса иксазомиба является метаболизм ферментами цитохрома P450 (CYP3A -42%) и некоторыми другими дополнительными путями [14]. Иксазомиб (Нинларо) коммерчески доступен в форме капсул по 2,3; 3 и 4 мг для орального применения.…”
Section: таблица 1 сравнительная характеристика одобренных ингибиторunclassified